The Effect of Cash Holding on Capital Structure of Companies Listed on the Indonesia Stock Exchange - Verano, Raka; Mantiri, Dessy; Veronica, Veronica; Lestari, Henny (Jurnal Ilmiah Manajemen Kesatuan, 2023)
This study discusses the factors that influence company performance in the manufacturing sector on the Indonesia Stock Exchange. The sample used was 20 companies engaged in the manufacturing sector listed on the Indonesia Stock Exchange (IDX) for five years from 2018-2022. The sampling technique used is purposive sampling and the analysis method used is panel data regression. The dependent variable used in this study is Cash Holding Ratio, while the independent variables are Current Ratio, Non-Current Ratio, Total Debt Ratio and with control variables namely Profitability, Firm Size, Dividend Rate, Liquidity. The results of this study indicate that (1) Current Ratio has no effect on Cash Holding Ratio. (2) Non-Current Ratio has no effect on Cash Holding Ratio. (3) Total Debt Ratio has no effect on Cash Holding Ratio. (4) Profitability has a negative effect on Cash Holding Ratio. (5) Firm Size has no effect on Cash Holding Ratio. (6) Dividend Rate has no effect on Cash Holding Ratio. (7) Liquidity has a positive effect on Cash Holding Ratio. The results of this study can be a consideration for companies in allocating corporate funding by paying attention to the use of debt as a source of capital to improve company performance, and consideration for investors in making decisions when investing in companies on the basis of considerations related to the level of use of debt as a source of capital in a company.